Formulation and Evaluation of Gastroretentive Floating Dosage Form of Lamivudine - Lalitha, Agastya (International Journal of Pharmaceutical & Biological Archive, 2021)
Introduction: Formulation of potent drug molecules as dosage form still draws continuous interest and challenges against its optimization toward pharmacokinetics parameters such as absorption, bioavailability, onset of action, and duration of action. Material: The consistent maintenance of plasma drug concentration within the therapeutic level for prolonged periods of time has been persisting as a challenge to the pharmaceutical field. Method: The conventional dosage forms are designed to be consumed by the patients two, three, or even 4 time a day, which ultimately results in non-compliance by the patient. Result: In accordance with the therapeutic objective, to design and evaluate hydrodynamically balanced non-effervescent floating drug delivery systems of lamivudine as controlled release modules, which prolongs the release rate of the drug while extending the residence time of the drug within the body environment and without causing undeliterious effects to the subject. Conclusion: The drugs with low biological half-life and unstable in the small intestine are good candidates for Gastroretentive dosage forms.